Improving social functioning and reducing social isolation and loneliness among people with enduring mental illness: Report of a randomised controlled trial of supported socialisation. (May 2015) - Sheridan, Ann J; Drennan, Jonathan; Coughlan, Barbara; O'Keeffe, Donal; Frazer, Kate; Kemple, Mary; Alexander, Denise; Howlin, Frances; Fahy, Anne; Kow, Veronica; O'Callaghan, Eadbhard
Background: This randomised controlled trial examined if for people with enduring mental illness, being supported to socialise leads to improved social functioning, increased self-esteem and extended social networks; a reduction in social isolation, social, emotional and family loneliness and a reduction in illness symptoms, namely depression. Methods: A prospective randomised controlled trial was undertaken from November 2007 to September 2011. Service users with a diagnosis of enduring mental illness (>18 years) were invited to participate. Participants were randomly allocated to intervention or control group conditions in a 1:1 ratio. Intervention group participants were matched with a volunteer partner, asked to engage in social/leisure activities for 2 hours weekly over a 9-month period, and received a €20 stipend monthly. Control group participants received a €20 monthly stipend and were asked to engage in a weekly social/leisure activity. Social functioning, the primary outcome, was measured using the Social Functioning Scale (SFS) at three time points (baseline, midpoint and endpoint). Findings: In all, 107 people completed this study. There were no significant differences between control and intervention groups at the commencement of the intervention on demographic characteristics or the main outcome measures of interest. Overall social functioning positively changed throughout the three time points from a mean of 99·7 (standard deviation ( SD ) = 15.1) at baseline, to a mean of 106.0 ( SD = 27.0) at the endpoint for the control group, and from a mean of 100·4 ( SD = 15.0) at Time 1 for the intervention group, to a mean of 104.1 ( SD = 23.4) at the endpoint for the intervention group. Conclusions: The intervention showed no statistical differences between the control and intervention groups on primary or secondary outcome measures. The stipend and the stipend plus volunteer partner led to an increase in recreational social functioning; a decrease in levels of social loneliness, in depression and in the proportion living within a vulnerable social network.